The Inflammatory Potential of the Diet is Directly Associated with Incident Depressive Symptoms Among French Adults. Issue 7 (1st June 2019) - Adjibade, Moufidath; Lemogne, Cédric; Touvier, Mathilde; Hercberg, Serge; Galan, Pilar; Assmann, Karen E; Julia, Chantal; Kesse-Guyot, Emmanuelle
ABSTRACT: Background: Low-grade chronic inflammation has been suggested to play a substantial role in the etiology of depression; however, studies on the prospective association between the inflammatory potential of the diet and depression are limited. Objective: The aim of this study was to investigate the association between the inflammatory potential of the diet (measured using the Alternate Dietary Inflammatory Index, ADII) and incident depressive symptoms. We also tested the potential modulating effect of sex, age, BMI, and lifestyle indicators. Methods: The study sample consisted of 26, 730 participants (aged 18–86 y) from the NutriNet-Santé study. Baseline ADII was computed using repeated 24-h dietary records collected during the first 2 y of the follow-up. Incident cases of depressive symptoms were defined by a Center for Epidemiologic Studies Depression scale ≥17 for men and ≥23 for women at least once during follow-up. HR and 95% CI were estimated using multivariable Cox proportional hazards models. Results: A total of 2221 incident cases of depressive symptoms were identified over a mean follow-up of 5.4 y. After accounting for a wide range of potential confounders, the highest quartile of the ADII was associated with a 15% (95% CI: 2, 31) increase in the risk of depressive symptoms compared with the lowest quartile. In the stratified analyses, associations were statistically significant only among women (HRquartile4 vs. quartile1 : 1.19; 95% CI: 1.02, 1.37), middle-age adults (HRquartile4 vs. quartile1 : 1.16; 95% CI: 1.00, 1.35), and participants with a BMI ≥25 (HRquartile4 vs. quartile1 : 1.29; 95% CI: 1.04, 1.60). Conclusions: Overall, a proinflammatory diet was associated with a higher risk of depressive symptoms, especially among women, middle-age adults, and participants with overweight or obesity. These findings contribute to the increasing scientific evidence showing a detrimental role of the proinflammatory diet. The NutriNet-Santé study is registered at clinicaltrials.gov as NCT03335644.